Understanding Oman’s policy toward regional conflicts - Mushegh Ghahriyan (Banber Arevelagitut'yan Instituti)
The study of Oman’s foreign policy attracts scholars because of its unique features. It undoubtedly differs from the foreign policies of other countries in the region. This paper focuses on Oman’s policy in three cases of regional conflicts: the Syrian war, the war in Yemen, and the crisis in Qatar in the context of regional changes and Saudi-Iranian rivalry. Oman pragmatically manoeuvres to mitigate threats emerging from the crises and wars in the countries of the Middle East.